Remote Work and the Psychosocial Work Environment: The Role of Contact - Mari Holm Ingelsrud; Vilde Hoff Bernstrøm; Wendy Nilsen (Nordic Journal of Working Life Studies)
Remote work is fundamentally changing the organization of work, replacing the physical work environment of the office and creating a spatial distance between colleagues. This article investigates the relationship between remote work frequency and three aspects of the psychosocial work environment (quantitative job demands, control, and social support) and to which extent the relationship is mediated by the frequency of contact with supervisors and co-workers. The Norlife Remote Work - Longitudinal Study (NorRemo-LS) of Norwegian employees (n = 2553) across four waves between February 2021 and September 2022 is analyzed using general structural equation modeling (GSEM). The results show that the extent of remote work is associated with increased schedule control. Remote work may diminish employee control and increase quantitative job demands if employees have less frequent contact with their supervisor. Less frequent contact with co-workers not only entails lower job control and less social support but also lower quantitative demands.